Citizens of Photography The Camera and the Political Imagination - Pinney, Christopher; Binaisa, Naluwembe; Buthpitiya, Vindhya; Kalantzis, Konstantinos; Selejan, Ileana Lucia; Young, Sokphea (Duke University Press, 2023)
Through contemporary ethnographic investigations of photographic practice in Nicaragua, Nigeria, Greece, India, Nepal, Sri Lanka, Bangladesh, and Cambodia, Citizens of Photography explores how photography offers access to forms of citizenship beyond those available through ordinary politics.